Social Media Dependency Dan Information Privacy Concerns Terhadap Switching Behavior Pada Media Sosial Tiktok - Azahra, Putri Rif’da Azmi; Saputri, Marheni Eka (eProceedings of Management, 2024)
The emergence of various new social media facilities causes dependence and worry for users. As a new social media,TikTok is currently one platform that users love. This research investigates users' transition from the TikTokapplication to a new one. The method used in this research applies a quantitative approach with a descriptive researchtype. The population used in this research is TikTok social media users in Indonesia with a sample size of 385respondents. The sampling used in this research was accidental sampling. Based on the results of research usingdescriptive analysis with the help of IBM SPSS 25 for Windows software, it shows that social media dependency andinformation privacy concerns have a significant simultaneous and partial effect on switching behavior. Keywords-privacy concern; social media dependency; switching behavior, and TikTok.